Tuning Molecular Chromophores of Isoreticular Covalent Organic Frameworks for Visible Light‐Induced Hydrogen Generation - Li, Wen; Ding, Xu; Yu, Baoqiu; Wang, Hailong; Gao, Zhuo; Wang, Xinxin; Liu, Xiaolin; Wang, Kang; Jiang, Jianzhuang (Advanced functional materials, 2022)
The functions of covalent organic frameworks (COFs) can be tailored by covalently reticulating advanced molecular modules into well‐defined porous ordered materials. Herein, four COFs, USTB‐7–USTB‐10, are prepared from the solvothermal reaction of photoactive tetraaldehydes, 5,5″‐(benzo[c]‐[1,2,5]thiadiazole‐4,7‐diyl)diisophthalaldehyde and 5,5″‐(naphtho[2,3‐c][1,2,5]thiadiazole‐4,9‐diyl)diisophthalaldehyde, with p‐phenylenediamine and benzidine, respectively. Comprehensive studies of powder X‐ray diffraction, theoretical simulation, and pore size distribution disclose their isoreticular 2D dual porous structures. In contrast to benzo[c][1,2,5]thiadiazole‐based chromophore, employment of naphtho[2,3‐c][1,2,5]thiadiazole‐based tetraaldehyde enables enlarged conjugation systems for USTB‐9 and USTB‐10, rather than USTB‐7 and USTB‐8. This, in combination with the longer benzidine unit, endows USTB‐10 with a porous structure with bigger pore size than that of USTB‐9, resulting in the highest photocatalytic hydrogen production rate of 21.8 mmol g−1 h−1 with the help of a Pt cocatalyst. Experimental and theoretical studies reveal the outstanding photocatalytic activity for USTB‐10 among the four COFs associated with the narrowed bandgap and increased charge‐carrier separation efficiency. The photocatalytic activities of a series of four isoreticular dual porous covalent organic frameworks toward hydrogen evolution reaction are adjusted by the direct change of bandgap and charge‐carrier separation efficiency by modular copolymerization strategy, and USTB‐10 exhibits the highest photocatalytic hydrogen production rate of 21.8 mmol g−1 h−1 among these four materials.